The Impact of Land Leasing and Farm Partnership on Community Economics - Hamidi, A. Luthfi; Ma'sumah, Siti; Adam, Ibni Trisal; Aprianto, Naerul Edwin Kiky (Journal of Ecohumanism, 2024)
Indonesia is an agricultural country, and the staple food of Indonesian people is rice. Rice is produced from rice fields. And not all rice field owners can manage their riches. In managing their rice fields, the owner of the rice fields can involve rice cultivators. The relationship between the owner of the rice fields, and the tenant farmers are divided into three, namely nggade, maro and, mertelu cooperation can also be carried out in dry land like coconut plantations, coffee and others. The results of this study concluded that the reasons for the respondents to cooperate with both Maro and Mertelu from the cultivator's point of view were: to supplement income to meet basic needs and other needs. In order to have a job, so as not to be unemployed. There are also those who reason because they were ordered by the land owner, rather than the land being unemployed. The reason for the people who do this is that they want to work on the rice fields but can’nt buy rice fields. There are also help people in need. One of the reasons for people who mortgage fields is that they need fast money but don't want to sell their fields. Empirically it is proven that Nggade, Maro and Mertelu can improve the economy.